ANALISIS PERWUJUDAN FUNGSI BIMBINGAN KONSELING PADA PESERTA DIDIK KELAS X SMA NEGERI 1 PONTIANAK - Lestari, Yuliana Dwi; Asrori, Mohammad; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe embodiment of Â guidance and counseling functions is an effort made by counseling techers in implementing counseling services such as understanding, prevention, poverty, and maintenance and development functions. These functions need to be implemented so that learners are able to maintain and develop their potential. The researcher wanted to know more deeply about the realization of guidance counseling functions in the students of class X IPS SMAN 1 Pontianak. The problem in this study is â€œHow is the embodiment of guidance counseling functions in students of class X IPS SMAN 1 Pontianak?â€. This study aims to obtain a description of the embodiment of guidance counseling functions in students of class X IPS SMAN Pontianak. The method used is descriptive with survey research from. The sample of this study was 53 people. This study use a quantitative approach. Data collecting techniques of this research is indirect communication techniques with questionnaire data collection tools and documentary study techniques with document data collection tools. Data analysis techniques using percentage calculation. Based on the results of data analysis embodiment guidance and counseling functions in students of class X IPS SMAN 1 Pontianak as a whole reached 80,54% with the category of â€œGoodâ€.Keywords: Embodiment Functions, Service, Guidance Counseling